O conservadorismo enquanto discurso político e religioso : uma análise ética em torno do diferente e de sua inclusão social - Klohn, Thiago Guagliardo (My University, 2026)
This thesis investigates conservatism as a political and religious discourse, analysing the extent to which this phenomenon operates as an ethical impediment to the social inclusion of minorities, referred to as "the different". It constitutes a philosophical-conceptual analysis, supported by a Foucauldian genealogical approach and a critical reading of public discourses (parliamentary statements, religious leadership, among others) as exemplars of power dispositifs. The inquiry proceeds from the premise that plurality is a constitutive and essential feature of humanity, manifesting both in the physical and psychic constitution of subjects and in their sociocultural expressions. In the second chapter, the work grounds this ontology of iversity through the debate between the One and the Multiple in Plato, difference as a creative force in Deleuze, and radical alterity in Levinas. It is argued that the failure to recognise the human being as multiple constitutes one of the underlying principles of conflicts that hinder the construction of a ore equitable world. In the third chapter, the analysis turns to the religious phenomenon, distinguishing subjective religious truth from institutionalised dogma. It is maintained that religious conservatism, by sacralising historical precepts, tends to articulate with forms of fundamentalism, fanaticism, and proselytism. Such practices are examined as operating through appeals to authority, aiming at the imposition of an absolute morality associated with the preservation of privileges and the restriction of the rights of minority groups. The chapter further explores politico-religious populism, examining how messianic forms of leadership mobilise believers within dynamics of power and domination. The fourth chapter employs the theoretical framework of Michel Foucault to map conservatism as a technology of governmentality. Through the concepts of pastoral power and biopolitics, the thesis describes how the modern state appropriates religious techniques for the direction of conduct in order to produce docile bodies. Contemporary examples in Brazil, such as disputes surrounding abortion and LGBTQIA+ rights, are analysed as illustrations of the use of religion as a dispositif of security and normalisation. Furthermore, the regime of post-truth is discussed, wherein moral narratives tend to displace the centrality of facts, sustaining a "culture of danger" that legitimises practices of social control. The ethical proposal for the twenty-first century, presented in the fifth chapter, advocates the valorisation of difference and social equity through Levinasian hospitality and Foucauldian "reflective indocility". Genuine inclusion requires the recognition of difference and the safeguarding of the secular character of the state. It is concluded that the human being may be understood as an unfinished process in constant becoming, such that social transformation is intrinsically linked to an ethical openness to human multiplicity. [resumo fornecido pelo autor]
Esta tese investiga o conservadorismo enquanto discurso político e religioso, analisando em que medida esse fenômeno atua como um entrave ético à inclusão social das minorias, referidas como "o diferente". Trata-se de uma análise filosófico-conceitual, com apoio genealógico foucaultiano e leitura crítica de discursos públicos (parlamentares, lideranças religiosas, entre outros) como exemplares de dispositivos de poder. A investigação parte da premissa de que a pluralidade é um traço constitutivo e essencial da humanidade, manifestando-se tanto na constituição física e psíquica dos sujeitos quanto em suas expressões socioculturais. No segundo capítulo, o trabalho fundamenta essa ontologia da diversidade através do debate entre o Uno e o Múltiplo em Platão, a diferença como potência criadora em Deleuze e a alteridade radical em Levinas. Argumenta-se que a falha em reconhecer o ser humano como múltiplo constitui um dos princípios dos conflitos que impedem a construção de um mundo mais equânime. No terceiro capítulo, a análise volta-se para o fenômeno religioso, distinguindo a verdade religiosa subjetiva do dogma institucionalizado. Sustenta-se que o conservadorismo religioso, ao sacralizar preceitos históricos, tende a se articular com formas de fundamentalismo, fanatismo e proselitismo. Tais práticas são examinadas como operando por meio do argumento de autoridade, visando à imposição de uma moralidade absoluta associada à manutenção de privilégios e à restrição de direitos de grupos minoritários. O capítulo explora ainda o populismo político-religioso, examinando como lideranças de caráter messiânico mobilizam o crente em dinâmicas de poder e dominação. O quarto capítulo utiliza o referencial teórico de Michel Foucault para mapear o conservadorismo como uma tecnologia de governamentalidade. Através dos conceitos de poder pastoral e biopolítica, a tese descreve como o Estado moderno estatiza técnicas religiosas de direcionamento das condutas para produzir corpos dóceis. Exemplos contemporâneos no Brasil, como as disputas em torno do aborto e dos direitos LGBTQIA+, são analisados como ilustrações do uso da religião enquanto dispositivo de segurança e normalização. Além disso, discute-se o regime de pós-verdade, no qual narrativas morais tendem a substituir a centralidade dos fatos, sustentando uma "cultura do perigo" que legitima práticas de controle social. A proposta ética para o século XXI, apresentada no quinto capítulo, defende a valorização do diferente e a equidade social através da hospitalidade levinasiana e da "indocilidade refletida" foucaultiana. A inclusão real exige o reconhecimento da diferença e a garantia da laicidade do Estado. Conclui-se que o ser humano pode ser compreendido como um processo inacabado em constante devir, de modo que a transformação social se vincula à abertura ética à multiplicidade humana. [resumo fornecido pelo autor]
Keywords: Religião e política - Filosofia; Conservantismo - Aspectos políticos; Conservantismo - Aspectos religiosos; Ética; Biopolítica; Integração social; Fundamentalismo religioso; Religion and politics- Philosophy; Conservatism - Political aspects; Ethics; Biopolitics; Social integration; Religious fundamentalism; Conservatism - Religious aspects